The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1548-2456.2009.00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Public Opinion on Nonwhite Underrepresentation and Racial Identity Politics in Brazil

Abstract: Brazil has an “African‐origin” population that is proportionally more than four times larger that of African Americans in the United States, but white Brazilians mostly dominate electoral politics. How do ordinary citizens explain this phenomenon? Drawing on a large‐sample survey of public opinion in the state of Rio de Janeiro, this article explores perceived explanations for nonwhite underrepresentation in the political arena. It also examines attitudes toward a particular black candidate, Benedita da Silva,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…5 Dancygier et al compare immigrant and native candidates in Sweden who have comparable individual resources and face similar political opportunity structures; they attribute the greater electoral success among natives to discrimination by party elites in the design of party lists. 6 Yet, it is rare to look at behavioral, institutional, and resource-based explanations for political inequality in a single study, as we do here. 7 Our results underscore that we should not study these alternatives in isolation: in our study, the importance of resource differentials is magnified by the inability of behavioral or institutional arguments to explain the patterns we document.…”
Section: Democracy and Descriptive Representationmentioning
confidence: 99%
“…5 Dancygier et al compare immigrant and native candidates in Sweden who have comparable individual resources and face similar political opportunity structures; they attribute the greater electoral success among natives to discrimination by party elites in the design of party lists. 6 Yet, it is rare to look at behavioral, institutional, and resource-based explanations for political inequality in a single study, as we do here. 7 Our results underscore that we should not study these alternatives in isolation: in our study, the importance of resource differentials is magnified by the inability of behavioral or institutional arguments to explain the patterns we document.…”
Section: Democracy and Descriptive Representationmentioning
confidence: 99%
“…Following Barack Obama’s re-election, all agreed that identity politics was a game-changer in the elections, and that articulations of collective victimhood, authenticity, and conflicting interests revealed that America was anything but ‘postracial’ (Goodwin, 2012; Younge, 2010). Although – in the wake of a successful multiracial movement, a growing presence of Latinos, and scientific statements against race – racial categories have blurred (Hochschild et al, 2012; Roth, 2012), political campaigns still heavily rely on racial framing (Bailey, 2009; Harvey-Wingfield and Feagin, 2012).…”
Section: Identity Politics Then and Nowmentioning
confidence: 99%
“…e.g.,Bueno and Fialho 2009;hunter and power 2007;Bailey 2009. 33 see guimarães telles 2004; hanchard 1999; twine 1998; also, Freyre 1980 also, Freyre [1933.34 telles 2004.…”
mentioning
confidence: 98%
“…9 e.g., acemoglu and Robinson 2008. 10 exceptions includeJohnson 1998 and Johnson 2006;Mitchell 2009a andMitchell 2009b;Bailey 2009; castro 1993;and soares and do Valle silva 1987.…”
mentioning
confidence: 99%